التمويل الإسلامي للمؤسسات الصغيرة والمتوسطة من أجل تحقيق التنمية المستدامة في الجزائر - فؤاد, عنون; حمزة, ضويفي; جمال الدين, سيليني (Université de M'sila, 2020)
تطرقنا في هذه الدراسة الى ضرورة انتهاج الدولة الجزائرية لخارطة طريق جديدة بدعم المؤسسات الصغيرة والمتوسطة، من خلال الاعتماد عليها واشراكها بصفة فاعلة ودائمة في بناء وتطوير الاقتصاد الوطني وتحقيق التنمية المستدامة، كل هذا من أجل خلق فرص شغل جديدة، وباعتبار المؤسسات الصغيرة والمتوسطة كفرص بديلة لاستخلاف الاقتصاد الريعي البترول وفي اطار إيجاد مصادر تمويل جديدة للتحديات القادمة. لكن ظهرت مشكلة التمويل المالي جليا لتكون حاجزا أمام نشأة وتطور عمل هذه المؤسسات، لأن من متطلبات التعاملات البنكية أي مصادر التمويل الأساسية بعد رأس المال لأصحاب هذه المؤسسات تميل لكل ما هو إسلامي خوفا من الوقوع في التعاملات الربوية، كل هذا ما يجبر أغلب هذه المؤسسات على التعامل مع البنوك التجارية الإسلامية أو بالمنتوجات الإسلامية في البنوك التجارية الكلاسيكية ان وجدت، و توصلنا في دراستنا الى ضرورة مواكبه التمويلات الإسلامية لرغبات المؤسسات من أجل تحقيق أهداف جل المتعاملين ومنه الوصول الى تحقيق التنمية المستدامة الأمثل في الجزائر. Abstract: In this study, we discussed the need for the Algerian state to adopt a new road map by supporting small and medium-sized enterprises, by relying on them and involving them effectively and permanently in building and developing the national economy and achieving sustainable development, all in order to create new jobs, and considering institutions Small and medium-sized enterprises as alternative opportunities to replace the oil economy and in the framework of finding new sources of financing for the challenges ahead. But the problem of financial financing has clearly emerged to be a barrier to the emergence and development of the work of these institutions, because one of the requirements of banking transactions, i.e. the basic sources of financing after capital for the owners of these institutions tend supplanted for all that is Islamic for fear of falling into riba-based transactions, all of which forces most of these institutions to Dealing with Islamic commercial banks or Islamic products in classical commercial banks, if any., In our study, we have found that Islamic finances must keep pace with the wishes of institutions in order to achieve the goals of most customers, including achieving optimal sustainable development in Algeria.
Keywords: المؤسسات الصغيرة والمتوسطة، التمويل الإسلامي ، البنوك التجارية الإسلامية، التنمية المستدامة.